Personal attributes, family influences, entrepreneurship education and entrepreneurship inclination among university students - Mustapha, Mazlina; Selvaraju, Maitilee (Penerbit Universiti Sains Malaysia, 2015)
This paper investigates the factors associated with entrepreneurial inclination among undergraduate students in Malaysian universities. Among others, the influences of personal attributes, family and peer, and entrepreneurship education on the students' inclination towards entrepreneurship are examined. Self-administered questionnaires were distributed to accounting students at three public universities in Klang Valley. About 178 questionnaires were completed and were found to be usable for the purpose of the study. Hierarchical multiple regression analysis and t-tests were employed to analyse the data. Generally, the results of the study indicate that the respondents have a positive inclination towards entrepreneurship. The hierarchical regression results show that personal characteristics, family influence, entrepreneurial education have positive and significant influence on the students' intention to be entrepreneurs when the variables are added into the equation. However, gender is not an important factor in influencing the students to choose entrepreneurship as their future career pathway.